Circular RNA HIPK3: A Key Circular RNA in a Variety of Human Cancers - Wen, Jingyuan; Liao, Jingyu; Liang, Junnan; Chen, Xiao-ping; Zhang, Bixiang; Chu, Liang (Frontiers in Oncology, 2020)
Circular RNAs (circRNAs), which act as initial factors and promoters in different diseases, are noncoding RNAs (ncRNAs) in eukaryotes. Accumulating studies have proven that dysregulation of circRNAs is relevant to the occurrence and development of multiple cancers. circHIPK3, as a member of circRNA, is frequently expressed in many diseases, such as diabetes, age-related cataract, idiopathic pulmonary fibrosis, preeclampsia, osteoblasts and retinal vascular dysfunction, leading to disease development and progression. In addition, circHIPK3 also serves an essential role in the occurrence and development of cancer. In current studies, many circHIPK3-related cancers have been identified, including nasopharyngeal carcinoma, gallbladder cancer, lung cancer, hepatocellular carcinoma, osteosarcoma, glioma, colorectal cancer, ovarian cancer, bladder cancer, prostate cancer, gastric cancer, oral squamous cell carcinoma and chronic myeloid leukemia. This review demonstrates the recent literature on the biological functions of circHIPK3 and expounds the molecular mechanisms of circHIPK3 in the abovementioned malignant tumors.